UJI DAYA HAMBAT EKSTRAK ETANOL KETEPENG CINA (Cassia alata L.) TERHADAP PERTUMBUHAN JAMUR Colletotrichum gloeosporioides - Pauline Destinugrainy Kasi; Ridha Yulyani Wardhi; Sunarti Cambaba; Ika Pitra Annisa (Cokroaminoto Journal of Chemical Science, 2020)
Colletotrichum gloeosporioides is a pathogenic fungus that attacks plants and causes anthracnose disease. Leaves of ketepeng cina (Cassia alata. L) have potential as a biological fungicide because they contain secondary metabolite which is collected as an antifungal. This study aims to know about the inhibitory effects of etanolic extract of ketepeng cina leaves on the growth of Colletotrichum gloeosporioides, and to determine the effective concentration of etanolic extract of ketepeng cina leaves in inhibiting the growth of Colletotrichum gloeosporioides. The treatment etanolic extract of ketepeng cina leaves used were: P0: 0% concentration, P1: 30% concentration, P2: 60% concentration and P3: 80% concentration. Fungal growth was observed on the 7th day after incubation. The results showed that the contribution of etanolic extract of ketepeng cina leaves could inhibit the growth of the fungus Colletottrichum glosporidies. The most effective concentration of etanolic extract of ketepeng cina leaves was 80%, with an average growth of Colletotrichum gloeosporioides diameter was 1.35 cm and suppressed the spread of hyphae